Building Islamic Economy Towards Golden Indonesia 2045 - Tukiran Tukiran; Muhammad Arhan Rajab; Ibnu Mas'ud (PT. Anagata Sembagi Education, 2024)
This study examines the strategic role of Islamic economics in supporting the achievement of the Golden Indonesia Vision 2045, which targets inclusive economic growth, poverty alleviation, global competitiveness, and sustainable development. Through the principles of social justice, equitable distribution of wealth, and wise management of natural resources, Islamic economics offers solutions that are in line with these goals. This study uses a mixed methods approach, combining quantitative surveys and qualitative interviews to explore the public and stakeholders' understanding of Islamic economics and the challenges and opportunities in its development. The results show that although the majority of respondents have a good understanding of Islamic economics, there are still barriers to the use of Islamic financial products, including a lack of understanding and access. In addition, interviews with entrepreneurs, academics, and policymakers reveal the importance of Islamic financial literacy as a key to expanding community participation. The study concludes that Islamic economics has great potential to drive equitable, inclusive, and sustainable growth, but supportive policies and broader education are needed to maximize its contribution to the Golden Indonesia Vision 2045.